Effect of early physical therapy interventions on post-operative ileus following abdominal hysterectomy - Zia, Zarfasheen; Huma Riaz; Iqra Imtiaz (Journal of the Pakistan Medical Association, 2023)
This study was conducted to determine the effect of early physical therapy intervention on symptoms of post-operative ileus after abdominal hysterectomy. This randomised control trial was carried out at the Railway General Hospital, Rawalpindi, Pakistan, from February 2021 to July 2021. Participants were randomly allocated to experimental (n=21) and control (n=21) groups using sealed envelope method. The experimental group received an enhanced physiotherapy rehabilitation plan of care consisting of patient education, breathing exercises, early mobilisation, connective tissue manipulation, and transcutaneous electrical nerve stimulation, while the control group only performed ambulation. The intervention was carried out during the first three days after surgery. Subjective measures were used to determine post-operative ileus. The study results conclude that enhanced early post-operative rehabilitation programme following abdominal hysterectomy has the potential to improve symptoms of post-operative ileus. Keywords: Connective tissue, Early ambulation, Hysterectomy, Ileus, Physical therapy, Rehabilitation.